Low content of highly reactive iron in sediments from Prydz Bay and the adjacent Southern Ocean: Controlling factors and implications for sedimentary organic carbon preservation - Huang, Wenhao; Guo, Xiaoze; Zhao, Jun; Li, Dong; Hu, Ji; Zhang, Haifeng; Zhang, Cai; Han, Zhengbing; Sun, Weiping; Sun, Yongge; Pan, Jianming (Frontiers in Marine Science, 2023)
Examining iron (Fe) speciation in marine sediments is critical to understand Fe and carbon biogeochemical cycling in polar regions. In this study, we investigated the speciation of Fe in sediments from Prydz Bay and the adjacent Southern Ocean, and examined the factors controlling Fe speciation and its relationship with total organic carbon (TOC). Our results reveal that unreactive silicate Fe (FeU) is the dominant pool of total Fe (FeT), followed by poorly reactive sheet silicate Fe (FePRS), reducible crystalline Fe oxides (Feox2), easily reducible amorphous/poorly crystalline Fe oxides (Feox1), and magnetite (Femag), with carbonate-associated ferrous Fe (Fecarb) being the smallest pool. The highly reactive Fe (FeHR)/FeT ratios (0.13 ± 0.06) in our study area are among the lowest end-member globally, primarily due to weak bedrock weathering and slow glacier melting. The Feox1/FeT ratios are similar to those in continental shelf and marginal seas containing highly weathered materials, while the Feox2/FeT ratios are significantly lower. This result implicates that low temperature inhibits the aging of iceberg melting-sourced Feox1 potentially, and accordingly the regulation of weathering on the FeHR/FeT ratio is mainly reflected in Feox2/FeT ratio. There are no significant correlations between TOC and FeHR, Fecarb, Feox1 or Feox2 in the research region. Four distinct patterns of TOC/FeHR ratio can be discerned by summarizing the global data set: (a) high TOC/FeHR ratios (> 2.5) are likely the result of high marine primary productivity and low chemically weathered source materials; (b) low TOC/FeHR ratios (< 0.6) are caused by high rates of FeHR inputs and OC remineralization; (c) mid-range TOC/FeHR ratios (0.6 – 2.5) typical of most river particulates and marginal sea sediments indicate the same FeHR and OC sources and/or interactions between each other; (d) both low TOC and FeHR content is the result of low marine primary productivity and weak chemical weathering. Our findings provide new insights into the relationship between FeHR and TOC in polar sediments.